Influence of cultivation sites on sterol, nitrate, total phenolic contents and antioxidant activity in endive and stem chicory edible products. (2nd January 2017) - D'Acunzo, Francesca; Giannino, Donato; Longo, Vincenzo; Ciardi, Marco; Testone, Giulio; Mele, Giovanni; Nicolodi, Chiara; Gonnella, Maria; Renna, Massimiliano; Arnesi, Giuseppe; Schiappa, Alessandro; Ursini, Ornella
Abstract: Chicories produce a wide range of vegetables with important nutritional value. We determined the variation of sterol, total polyphenol, nitrate contents and antioxidant capacity (SC, TPC, NC, AC) in endive leaves and stem-chicory novel vegetables, cultivated in two Italian regions. Within a given area, the SC was similar in smooth- and curly leafed endives (106.3–176.0 mg/kg FW); sitosterol and stigmasterol were major fractions (45–56 versus 38–43%). The stem SC was independent of landrace (101.5–118.6 mg/kg FW); sitosterol prevailed on stigmasterol and fucosterol (73–76 versus 12–14% versus 8–9%); the latter reached 15.7 mg/kg FW, conferring value as potential antidiabetes food. The planting site affected the AC and TPC of endives (893.1–1571.4 μmTE/100 g FW, 30.8–76.1 GAE100/g FW) and chicory stems (729.8–1152.5 μmTE/100 g FW; 56.2–124.4 GAE100/g FW), while the NC was recurrently below dangerous thresholds. PCA showed that environment was the major cause of variation, though it modestly affected these parameters.